Potential distribution of crop wild relatives under climate change in Sri Lanka: implications for conservation of agricultural biodiversity - Ratnayake, Sujith; Kariyawasam, Champika; Kumar, Lalit; Hunter, Danny; Liyanage, Athula (Elsevier, 2021)
The global population is growing rapidly and food production needs to be stepped up substantially to supply the additional demand expected by projected increased population. Further, climate change is expected to exert considerable pressure on global agriculture and food production. Crop wild relatives (CWR), which possess large untapped genetic diversity, can provide vital genetic material for future crop improvement. At present, this important category of plants is at risk due to anthropogenic climate change and other human-mediated changes i.e., habitat destruction. Therefore, it is important to study and understand the vulnerability of CWR to climate change, their potential distribution, and range dynamics for their conservation. Here we use Maxent algorithm to simulate the potential distribution across nine CWR species belonging to four crop genera, Cinnamomum, Piper, Vigna and Oryza in Sri Lanka and investigate how the predicted potential suitable areas change under climate change. Our findings indicate that species response to climate change varies among species studied, even within the same genus. Many species are predicted to decrease their suitable habitat by 2050, suggesting that these species are highly vulnerable to climate change impacts. The study identifies potential CWR rich areas in the country for future in situ conservation. Our findings facilitate decision-makers to make evidence-based decision-making for better management of CWR in Sri Lanka.